ICT, Financial Development and Economic Growth in ASEAN Countries - Noraina Mazuin, Sapuan; Mohammad Rahmdzey, Roly (European Publisher, 2020)
This paper examines the impact of and relationship between ICT diffusion, financial development and economic growth in selected ASEAN countries. In order to investigate this query, panel data estimations are used by utilizing data from 2003 to 2017. The finding indicates that ICT diffusion and financial development have an impacton economic growth of ASEAN countries. Consequently, the findings of the study could be an aid for the future researcher to study deeper in this research.The policymakers need to take a further initiative to improve the information technology and its applications in these countries. To gain benefit from the ICT drivers of economic growth, policymakers should enact several important policies that permit the development of financial sectors, provide a more convenient regulatory and institutional environment, increase economic openness, prioritize the allocation of resources to the development of ICT infrastructure, and contain the negative effects of inflation and government consumption.